2018
DOI: 10.1016/j.jcma.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of school educating program for betel quid chewing: A pilot study in Papua New Guinea

Abstract: A great achievement was gained by a short time of education. To prevent the incidence and mortality of oral cancer in Papua New Guinea, education programs should be arranged aggressively and effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
0
23
1
Order By: Relevance
“…Betel nut, as a controversial food, can not only create excitement by chewing but also harm human's health. It has been reported that more than 600 million people have enjoyed this food . So this biomass wastes have great appeal in the preparation of activated carbon materials.…”
Section: Introductionmentioning
confidence: 73%
“…Betel nut, as a controversial food, can not only create excitement by chewing but also harm human's health. It has been reported that more than 600 million people have enjoyed this food . So this biomass wastes have great appeal in the preparation of activated carbon materials.…”
Section: Introductionmentioning
confidence: 73%
“…For example, an education program for betel nut chewing for school children was conducted in Papua New Guinea in 30-minute sessions. The 150 school children who attended the program showed an increase in knowledge of the product [41]. It should be noted that the motivation to start or quit, however, was low, suggesting more intensive education was needed [41].…”
Section: Discussionmentioning
confidence: 99%
“…The 150 school children who attended the program showed an increase in knowledge of the product [41]. It should be noted that the motivation to start or quit, however, was low, suggesting more intensive education was needed [41]. Another clustered randomized trial assessed the effectiveness of a school-based smokeless tobacco intervention among 1,327 Karachi school children.…”
Section: Discussionmentioning
confidence: 99%
“…Instagram, as a form of visual social media, is highly favored by teens and young adults (Clement, 2019). In some regions, betel nut use starts at a young age and their first experience may begin in elementary school (Chen, Hsieh, Chen, Kao, Chen, 2018;Gupta & Warnakulasuriya, 2002;Shah, Merchant, Lubi, & Chotani, 2002). In addition, countries that have pan masala, a commercially produced betel nut product, heavily advertise to children and adolescents (Malik, Chowdhury & Chauhan, 2002).…”
Section: Future Researchmentioning
confidence: 99%